Multiplex PCR detection of the antibiotic resistance genes in Staphylococcus aureus strains isolated from auricular infections - Zmantar, T; Chaieb, K; Ben Abdallah, F; Ben Kahla-Nakbi, A; Ben Hassen, A; Mahdouani, K; Bakhrouf, A (Folia microbiologica, 2008)
Thirty-five Staphylococcus aureus strains from auricular infections were isolated. The identification of strains was confirmed by Api ID 32 Staph strips, the antibiotic susceptibility test was performed using ATB Staph kit. PCR assay was used to detect the oxacillin resistance gene (mecA) and the erythromycin genes (ermA, ermB, ermC, msrA and mef). The susceptibility profile of all strains revealed a low resistance level to oxacillin and erythromycin. The PCR results show that 60 % of the strains are mecA positive. The frequency of erythromycin genes was: ermA (+) 22.8 %, ermB (+) 45.7, ermC (+) 17.1, msrA (+) 28.6. The mef gene was not detected in any strain. No correlations between genotypic and phenotypic methods for the determination of oxacillin and erythromycin resistance was found. However, multiplex PCR technique was shown to be a fast, practical and economic technique for the detection of methicillin-and erythromycin-resistant staphylococci.
Keywords: polymerázová řetězová reakce; stafylokokové infekce; methyltransferasy; Bacterial Proteins; Staphylococcus aureus; Erythromycin; Penicillin-Binding Proteins; Drug Resistance, Bacterial; membránové proteiny; antibakteriální látky; Membrane Proteins; proteiny vázající penicilin; lidé; Anti-Bacterial Agents; Humans; bakteriální léková rezistence; Methyltransferases; erythromycin; bakteriální proteiny; Staphylococcal Infections; Ear Auricle; Polymerase Chain Reaction; Oxacillin; ušní boltec; oxacilin